Room Temperature Grown High‐Quality Polymer‐Like Carbon Gate Dielectric for Organic Thin‐Film Transistors. (4th February 2016) - Feng, Linrun; Anguita, José V.; Tang, Wei; Zhao, Jiaqing; Guo, Xiaojun; Silva, S. Ravi P.
Abstract : Room temperature plasma‐enhanced chemical vapor deposited (PECVD) polymer‐like carbon (PLC) dielectric with outstanding surface and electrical characteristics is used as the gate dielectric in organic thin‐film transistors. The devices show state‐of‐the‐art overall electrical performance on glass and flexible substrates.